Testing Microstructure Theory on Karachi Stock Exchange - Nazir, Nadeem; Raza, Hamad (Information Management and Business Review, 2017)
We are analyzing the various measures of liquidity of Karachi Stock Exchange Market on the basis of microstructure theory. The concept of microstructure is focusing on the difference between the supply price and demand price of securities in any market. In other words, the price formation of the bid-ask spread is based on the supply and demand prices. Empirical studies conducted by different researchers have made a lot of contribution in this regards. As they concluded that bid-ask spread is constituted on the basis of different theories of liquidity. Historical background of microstructure literature shows that bid–ask spread constitutes the fundamental measure of the liquidity in any market. As a result of this it contributes to identify the best structure of stock market. There may be other admitted measures of liquidity. In the opinion of different researchers the internationally accepted measures of liquidity formation in any market include the Lambda, Turnover of the concerned security, Depth of that market, The Cost of Trip, Trade of security, etc. And they work as strong indicators of liquidity. Our study is a contribution to the literature as we try to explore those correlated variables that can be significantly and sequentially change. And they are serving a measure of the individual’s securities that are already traded in Karachi Stock Exchange Market. These admitted variables of our study are trading volumes of securities, number of transactions in the market, security return, volatility of securities prices, arrival of new information etc. we take a sample of 350 quoted securities in Karachi Stock Exchange Market, from 1990-2015. As far as result is concerned, depth showed a negative correlation with all spread measures in the Karachi Stock Exchange Market. But at the same time, perfect positive correlations are shown between spread measures in the analysis. It is a perfect proof of existence and validity of these liquidity measures in KSE. The results is evidencing that the arrival of new information, return on investment, volume of traded securities; are contributing a lot to explain significantly the sequential changes in KSE. At the same time various measures of the securities regarding liquidity are proving and confirming the previous researcher’s claim. In the end, analysts are in a better position to explain that the arrival of new information from different sources and different groups is functioning as a principal aspect for the variant contributories of liquidness of the Karachi Stock Exchange.